Can Social Capital Investment Reduce Poverty in Rural Indonesia? - Rustiadi, Ernan; Nasution, Ahmadriswan (International Journal of Economics and Financial Issues, 2017)
This study investigates the impact of social capital investment on the poverty of rural households in Indonesia using nationally representative datasets, namely Susenas 2012. Employing a logistic regression model to examine the effect of social capital on household poverty, this study tests whether the ownership of social capital reduces households' probability of being poor. The analysis shows that the effect of social capital on decreasing the probability of a rural household being poor is higher than that of human capital. The findings imply that, compared to other factors, social capital is the most important in reducing household poverty. Therefore, government agencies, the private sector, and other stakeholders should encourage investment in households' social capital to accelerate poverty reduction in Indonesia, complementary to other forms of “conventional” capital accumulation. Keywords: poverty, social capital, rural household, Indonesia, logistic regression JEL Classifications: C13, I32, R58